2020
DOI: 10.1099/ijsem.0.004197
|View full text |Cite
|
Sign up to set email alerts
|

Luteimonas gilva sp. nov., isolated from farmland soil

Abstract: A Gram-stain-negative, rod-shaped bacterium, strain H23T, was isolated from farmland soil sampled in Enshi City, Hubei Province, PR China. The isolate grew optimally at 28–32 °C, pH 8.0 and with 0.5 % (w/v) NaCl. Based on the results of 16S rRNA gene sequence and phylogenetic analyses, strain H23T belonged to the genus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…The quality of genome was evaluated using CheckM [32], which showed that the assembled genome completeness value was 100.0 % and the contamination was 0.69 %, thereby meeting the standards of genome data [33]. The genomic DNA G+C content was 69.3 mol%, which is in the range of genomic DNA G+C contents of the genus Luteimonas (64.3–73.4 %) [2]. The AAI values are shown in Table S2.…”
Section: Genome Featurementioning
confidence: 99%
See 4 more Smart Citations
“…The quality of genome was evaluated using CheckM [32], which showed that the assembled genome completeness value was 100.0 % and the contamination was 0.69 %, thereby meeting the standards of genome data [33]. The genomic DNA G+C content was 69.3 mol%, which is in the range of genomic DNA G+C contents of the genus Luteimonas (64.3–73.4 %) [2]. The AAI values are shown in Table S2.…”
Section: Genome Featurementioning
confidence: 99%
“…chenhongjianii 100111 T [7], L. terrae JCM 30122 T [45] and other strains in the genus Luteimonas [2].…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
See 3 more Smart Citations